Kecenderungan Masyarakat Memilih Lembaga Penyelesaian Sengketa Ekonomi Syariah. - Nurhasanah Nurhasanah; Hotnidah Nasution (Universitas Islam Negeri Jakarta, 2016)
The People’s Choice in The Completion of Sharia Economic Dispute. Background research is the fact that lack of sharia economic cases filed and decided by the institution of litigation and non-litigation. This research is exploratory research that uses a qualitative approach to explore facts sharia law in an economic context. Data in the form of a questionnaire/questionnaire is processed only to describe the percentage of sharia economic community propensity choose dispute resolution institutions. This description is preliminary data that drove researchers to explore the points required questions in the interview. Mismatch between quantitative data processed by the facts on the ground shows that people choose a wide selection of sharia economy in resolving disputes.DOI: 10.15408/ajis.v16i2.4457